Relação entre inflamação e alterações musculares na COVID-19: um estudo em pacientes adultos e idosos - Ramacciotti, Paulo Magalhães Gomes (Universidade Federal de São Carlos, 2023)
Muscular changes in COVID-19 are common, but their causes and severity are still debated. Pathophysiology is controversial, with the main hypotheses being either a direct effect of the virus or an indirect injury due to inflammation. Some studies suggest that age, comorbidities, and disease severity may mediate the relationship between inflammation and muscular changes. Objectives: This study aims to investigate the relationship between inflammation and muscle changes among adults and elderly people hospitalized with COVID-19, and whether age, comorbidities (updated Charlson Comorbidity Index, uCCI), and disease severity (Modified Early Warning Score, MEWS) moderate this relationship. Methods: A study with 155 hospitalized adults with COVID-19 (May to December 2020) measured clinical and laboratory parameters on hospital admission. Participants were grouped based on myalgia, myositis, or rhabdomyolysis and compared. Moderation analysis assessed age, comorbidities, and disease severity as moderators of the relationship between inflammatory parameters and muscular changes (myalgia and myositis separately). Logistic and negative binomial regressions were used to analyze factors associated with myalgia, myositis, and serum CK levels. Results: Of the patients evaluated, 34.8% had symptoms of myalgia, 16.8% myositis, and 3.2% rhabdomyolysis. Patients with myalgia were younger and had higher peripheral oxygen saturation, higher serum albumin and C-reactive protein, and lower IL-2 and IL-6. Logistic regression showed a significant association between age and myalgia in the multivariable model, including MEWS and uCCI scores, IL-2 and IL-6. Regarding myositis, only the laboratory parameters showed significant differences, with lower platelet count and higher serum creatinine, CRP, IFN-γ, IL-6, IL-10, and TNF- α. Logistic regression showed that only myalgia symptoms were significantly associated with myositis in the multivariable models, including age, MEWS, uCCI, and serum levels of IFN-γ, IL-6, IL-10, and TNF- α. The heterogeneity of the sample may have caused the significant association to cease in the adjusted models. Serum CK levels showed a significant association with MEWS score and serum levels of IFN-γ in a negative binomial regression, including age, MEWS, uCCI, and serum levels of IFN, IL-2, IL-4, IL-6, IL-10, and TNF. All five patients with rhabdomyolysis reported myalgia, had advanced age, low uCCI score, and moderate MEWS score. Conclusions: Muscular changes are frequent in adults and older adults who contracted COVID-19. To identify disease severity and serum IFN-γ levels associated with abnormal CK levels, myalgia can be used as an effective tool. Although the relationship between inflammation and muscular changes is still unclear, age, comorbidities, and disease severity must be considered adjustment variables. It is imperative to detect and treat myalgia complaints early. For older patients who may not complain of myalgia, the MEWS score can assist in the diagnosis. Our study has created a more accurate flowchart for investigating myalgia in patients with COVID-19 than the current literature offers. Health professionals should prioritize comprehensive assessments of clinical symptoms and laboratory tests when assessing COVID-19 patients.
Relationship between inflammation and muscle changes in COVID-19: a study in adult and elderly patients
Keywords: SARS-CoV-2; COVID-19; Mialgia; Miosite; Rabdomiólise; Inflamação; Citocinas; Adulto; Idoso; Myalgia; Myositis; Rhabdomyolysis; Inflammation; Cytokines; Aged; CIENCIAS DA SAUDE::MEDICINA